Prospective mathematics teachers’ collective identity work: navigating failure experiences and concerns about relating to students - Lutovac, Sonja; Havia, Johanna (NOMAD Nordic Studies in Mathematics Education, 2024)
The present study explores the collective identity work of prospective secondary mathematics teachers as they engage with their experiences of failure and success. The findings show how they navigate concerns about relating to students, resulting in failure-provoking or failure-reducing collective identity work. The prospective teachers’ perspectives arising from these distinct types of collective identity work are discussed as they might impact their development and future instruction, especially due to the absence of self-development strategies. This study highlights the need to build prospective mathematics teachers’ ability and confidence to relate to students unlike themselves and to problematise their seemingly unproblematic learning experiences and perspectives they co-construct in the collective identity work.